Optimizing delivery performance of a multi-Hop ad-hoc wireless network - Sum, Kah Ruay. (2011)
Ad hoc networking allows portable mobile devices to establish communication independent of a central infrastructure. However, the fact that there is no central infrastructure and that the devices can move randomly gives rise to various kind of problems, such as routing and security. In this report, the problem of routing is considered.